2012
DOI: 10.2147/cmar.s15545
|View full text |Cite|
|
Sign up to set email alerts
|

Reappraisal of the role of dolasetron in prevention and treatment of nausea and vomiting associated with surgery or chemotherapy

Abstract: Chemotherapy-induced nausea and vomiting and postoperative nausea and vomiting are one of the most frequent but also very concerning consequences for patients undergoing chemotherapy or surgical procedures under general anesthesia. There are a variety of mechanisms involved in the activation of nausea and vomiting. Serotonin, a ubiquitous central and peripheral neurotransmitter, is thought to be the predominant mediator of the perception of nausea and triggering of the vomiting response in both the brain and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Serotonin is an ubiquitous central and peripheral neurotransmitter thought to be the predominant mediator of the perception of nausea and triggering of the vomiting response ( 18 ). This occurs in both the brain and the periphery via the serotonin 5-hydroxytryptamine type 3 [5-HT(3)] receptor pathways ( 19 ). Palonosetron, compared to older 5-HT3 receptor antagonist, such as ondansetron, granisetron, dolasetron, and ramosetron, has higher receptor binding affinity and longer plasma half-life (40 h) ( 3 , 6 – 8 , 13 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin is an ubiquitous central and peripheral neurotransmitter thought to be the predominant mediator of the perception of nausea and triggering of the vomiting response ( 18 ). This occurs in both the brain and the periphery via the serotonin 5-hydroxytryptamine type 3 [5-HT(3)] receptor pathways ( 19 ). Palonosetron, compared to older 5-HT3 receptor antagonist, such as ondansetron, granisetron, dolasetron, and ramosetron, has higher receptor binding affinity and longer plasma half-life (40 h) ( 3 , 6 – 8 , 13 , 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical research shows that postoperative nausea and vomiting (PONV) is primarily caused by the use of inhalational anesthesia and opioid analgesics [6]. Studies have shown that the incidence of PONV is reduced by the use of antiemetic drugs such as 5-HT3 receptor antagonists (e.g., dolasetron) and/or total intravenous anesthesia [79]. However, despite impressive advances in the field of anesthesia, PONV remains an unpleasant postoperative experience that must be considered.…”
Section: Introductionmentioning
confidence: 99%
“… 30 In our study Midazolam was commonly utilized drugs similar to finding Sheen MJ, et al 31 study whereas these findings differ from the studies of Patil A, 32 Biswas P, et al 30 where the most commonly used anxiolytic was alprazolam. Here the glycopyrrolate 352 (88%) has been utilized which were more potent than atropine, used routinely as a pre-medication purpose and have less risk to the cardiovascular system, better control of oropharyngeal secretions during reversal stage 8 when compared to Zeev N and Mirakur RK, et al where atropine was the most commonly used. 33 , 34 Another most important drugs utilized in our study as a pre-anesthetic medication was Ondansetron (69.0%) from antiemetic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…7 To minimized the PONV several new drugs have been introduced but the incidence rate remains significantly high, ranging from 30%-35%. 8 So to reduce it or to improve and for better prophylaxis combinations of drugs are used. 9 14 …”
Section: Introductionmentioning
confidence: 99%